Flowers of the African Diaspora: An approach to their contribution to cultural management and cultural rights - Araya-Araya, Karla (2022)
This article offers a general analysis of the contributions of the “Festival Flores de la Diáspora Africana”, especially in the field of different cultural knowledges. Briefly, it is theoretical positioned under the tenants of pluriculturalism focusing on the cultural rights and the management of culture of the afro descendant peoples in Costa Rica and America mainly. In this respect, it is presented a synthesis of the work that, as a cultural promoter, the Festival has visualized in areas such as music, literature, photography, painting, dance, singing, plastic arts, politics, religion, fashion, and gastronomy. Finally, it is concluded that this Festival has become a transnational platform for populations traditionally excluded from the national imaginary to vindicate their contributions in society, so that cultural rights cease to be a discursive category of low impact for marginalized groups as the afro descendant diasporas.